Advances in Cryptology ASIACRYPT 2000 00 : 6th International Conference on the Theory and Application of Cryptology and Information Security Kyoto, Japan, December 37, 2000 Proceedings - Okamoto, Tatsuaki (Lecture notes in computer science, 2000)
This book constitutes the refereed proceedings of the 6th International Conference on the Theory and Application of Cryptology and Security, ASIACRYPT 2000, held in Kyoto, Japan in December 2000. The 45 revised full papers presented together with two invited contributions were carefully reviewed and selected from a total of 140 submissions. The papers are organized in topical sections on cryptanalysis, digital signatures, cryptographic protocols, number-theoretic algorithms, symmetric-key schemes, fingerprinting, zero-knowledge and provable security, Boolean functions, pseudorandomness, and public-key encryption and key distribution.